Reforming Pension Payments in Higher Education Institutions: A Study of the Defined Benefit Pension System in Pakistan (Journal of Asian Development Studies, 2025)
The Defined Benefit (DB) pension system operates under a Pay-As-You-Go (PAYG) framework, providing guaranteed post-retirement income and family pension benefits to Government Employees worldwide. However, rising pension liabilities, demographic shifts, and limited fiscal space have rendered the system financially unsustainable. Pakistan is not out of this problem, and Higher Education Institutions (HEIs) are particularly affected, as an increasing proportion of their recurrent grants is diverted toward pension obligations, constraining academic and developmental activities. While global pension reforms are well documented, the perspectives of operational pension administrators within Pakistan's HEIs remain largely unexplored. This study investigates sustainable reforms to optimise the DB pension payment system in HEIs. A qualitative multiple-case study design was used, including in-depth interviews with directors of finance, pension officers, auditors, and members of the HEC Board of Governors (BoG), supported by an extensive literature review. Using thematic analysis, both pre-empirical (literature-driven) and post-empirical (field-driven) frameworks were developed, identifying 25 additional mechanisms for controlling pension payments. The study proposes a comprehensive, evidence-based framework to assist policymakers, HEIs, and governing authorities in strengthening the financial sustainability of the DB pension system while ensuring the welfare of current and future employees.